Work force retention: Role of work environment, organization commitment, supervisor support and training & development in ceramic sanitary ware industries in India - Umamaheswari S; Jayasree Krishnan (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Although retention of employees has become hot topic in this career turbulent era, practically no empirical research is carried out in the fast growing ceramic sector till now and this research fills the gap in the literature. The literatures surveys reported that organization commitment is an important determinant of retention and work environment, supervisor support and training and development are the most relevant antecedents increasing commitment towards organization. This paper examines the impact of the above factors over organization commitment and explores the effects of organization commitment on retention, and verifies the mediating effect of organization commitment on the relationship between proposed factors and retention. Design/methodology/approach: A survey was completed by 416 employees working in five ceramic sanitary ware factories located at different places in India. Questionnaire consisting of items adopted from previous researches were used to collect data. The selection of respondents was based on the simple random sampling. Findings: Findings reveals that organization commitment influences retention and all the above factors enhances it. Moreover organization commitment partially mediates the relationship between proposed factors and retention. However multiple regression analysis indicated that training and development did not have any notable influence on retention. Limitations: This study was conducted in a particular country and also in a particular sector of manufacturing industry, which limits generalization .Possibility of bias towards their organization and assumption that respondents know about their organization are other limitations. Implications: This paper offers recommendations to HR(Human resource) managers that they should extend their support to work environment, supervisor support and training and development in order to generate better relationship with employees and to reduce their likelihood of leaving the company. Originality/value: This article makes significant contribution to most turnover prone Indian environment, highlighting the important factors to be given priority for employee's retention.
Keywords: 650; work environment; supervisor support; training and development; organization commitment; employee retention